Meeting the Sustainable Development Goal of Good Health and Well-Being by European Union Countries in 2017 - Iwona Konarzewska (Comparative Economic Research, 2020)
In September 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development, which includes 17 Sustainable Development Goals (SDGs). One of them, Goal 3, is defined as: Ensure healthy lives and promote well-being for all at all ages. In the paper, we have considered the indices proposed by Eurostat, which help to measure the level that the targets achieve. We present the dynamics of indices over the period 2002–2017. Multi-criteria statistical analysis for 28 EU countries was conducted using data up to 2017 to show how much EU countries are diversified and to present rankings of countries on their way to achieving the good health and well-being status of their citizens. The results are compared with a global SGD-Sub-Index for Goal 3, developed by Sachs et al. (2018).